2000
DOI: 10.1073/pnas.97.6.2503
|View full text |Cite
|
Sign up to set email alerts
|

Zinc transfer potentials of the α- and β-clusters of metallothionein are affected by domain interactions in the whole molecule

Abstract: The ␣-and ␤-polypeptides of human metallothionein (isoform 2), obtained by chemical synthesis, were converted into their respective zinc͞thiolate clusters, and each domain was investigated separately. Proton titration data for the N-terminal ␤-domain fit a simple model with three ionizations of the same apparent pK a value of 4.9 and a collective binding constant for zinc of 5 ؋ 10 ؊12 M at pH 7.0. The zinc cluster in the C-terminal ␣-domain is more stable than that in the ␤-domain. Its pH titration is also mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 37 publications
5
111
0
Order By: Relevance
“…The degree of pH change necessary to cause an effect on Zn 2+ handling, by contrast, significantly exceeds that reported to be caused by Baf. A pH drop below 6.7 is required to trigger an increase in intracellular Zn 2+ according to one set of studies (Kiedrowski, 2012), whereas another set has shown that metallothioneins release Zn 2+ only after cytoplasmic pH drops below 5.0 (Jiang et al, 2000). Thus, the increase in cytoplasmic Zn 2+ caused by Baf likely correlates with the loss of lysosomal function, rather than cytosolic pH changes.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of pH change necessary to cause an effect on Zn 2+ handling, by contrast, significantly exceeds that reported to be caused by Baf. A pH drop below 6.7 is required to trigger an increase in intracellular Zn 2+ according to one set of studies (Kiedrowski, 2012), whereas another set has shown that metallothioneins release Zn 2+ only after cytoplasmic pH drops below 5.0 (Jiang et al, 2000). Thus, the increase in cytoplasmic Zn 2+ caused by Baf likely correlates with the loss of lysosomal function, rather than cytosolic pH changes.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in properties however are apparent when comparing the full-length human MT2 protein with its two separate domains in vitro. The fully metal ion loaded full-length protein was found to be more stable towards oxidation and Zn II transfer [52], and remetallation studies with the apo-forms and As III revealed the faster metallation of the full-length form [53]. In addition, the apparent pK a values of the Cys residues in the Zn II -and the Cd II -forms, which are indicative for the metal ion affinities of the proteins, are lower for the full-length human MT2 compared to the average values obtained from separate measurements with the individual domains [52].…”
Section: Influence and Potential Role Of The Cys-devoid Linker Regionmentioning
confidence: 99%
“…The fully metal ion loaded full-length protein was found to be more stable towards oxidation and Zn II transfer [52], and remetallation studies with the apo-forms and As III revealed the faster metallation of the full-length form [53]. In addition, the apparent pK a values of the Cys residues in the Zn II -and the Cd II -forms, which are indicative for the metal ion affinities of the proteins, are lower for the full-length human MT2 compared to the average values obtained from separate measurements with the individual domains [52]. In summary, while the influence of the length of the linker region is less clear as variations of the amino acid composition might have a difficult to predict influence, it seems obvious that the physical connection of both domains plays a crucial role for the stability of the protein.…”
Section: Influence and Potential Role Of The Cys-devoid Linker Regionmentioning
confidence: 99%
“…Unfortunately, the binding and release kinetics of Zn 2ϩ with MT/T are still poorly understood, which, in turn, limits our understanding of its role as a cytosolic Zn 2ϩ buffer and/or chaperone. Studies of binding and release kinetics of the MT-2 isoform have suggested that the two domains differ significantly in Zn 2ϩ affinity (33,39). Two different Zn 2ϩ transporter gene families [solutelinked carrier (SLC) 39 and SLC30] have been identified; each family probably has a unique transport mechanism, function, and cellular location.…”
Section: ϩ Ionophore (Pyrithione) or Metal Chelators [Edta Clioquinmentioning
confidence: 99%